2008
DOI: 10.1002/aic.11428
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale characterization framework for sorption enhanced reaction processes

Abstract: in Wiley InterScience (www.interscience.wiley.com).A multiscale simulation and characterization framework has been developed for sorption enhanced reaction processes with heterogeneous multifunctional catalysts with sorption properties. Particles with in situ catalytic and sorption functionalities have obvious advantages in achieving high-purity and productivity. These processes are strongly limited by diffusion inside particle. In order to tackle this problem a more detailed characterization at particle level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Broda et al [194] For large-scale hydrogen production units where mass transfer limitations can significantly affect the process efficiency, the catalyst-sorbent mixing configuration is an important parameter to be considered. Besides a physical admixture of catalyst with sorbent, hybrid catalyst-sorbent patterns which integrate the catalytic reaction and the CO 2 sorption in a single pellet can present some advantages such as the elimination of mass diffusional limitation and the reduction of reactor volume [197,198]. Several studies have been performed on the development of hybrid catalyst-sorbent materials for SESMR process [199][200][201][202][203][204][205].…”
Section: Application Of Cao-based Sorbents In Sesmrmentioning
confidence: 99%
“…Broda et al [194] For large-scale hydrogen production units where mass transfer limitations can significantly affect the process efficiency, the catalyst-sorbent mixing configuration is an important parameter to be considered. Besides a physical admixture of catalyst with sorbent, hybrid catalyst-sorbent patterns which integrate the catalytic reaction and the CO 2 sorption in a single pellet can present some advantages such as the elimination of mass diffusional limitation and the reduction of reactor volume [197,198]. Several studies have been performed on the development of hybrid catalyst-sorbent materials for SESMR process [199][200][201][202][203][204][205].…”
Section: Application Of Cao-based Sorbents In Sesmrmentioning
confidence: 99%
“…A conventional Ni-based steam reforming catalyst and hydrotalcite sorbent are used in several modeling studies to theoretically demonstrate the performance of sorption-enhanced steam reforming process [5][6][7][8][9][10][26][27][28]. Xiu et al [6] simulated the process in a five-step, one fixed bed reactor using a multi-component system with overall mass and energy balances, pressure drop, and nonlinear adsorption equilibrium for CO 2 over hydrotalcite.…”
Section: Introductionmentioning
confidence: 99%
“…There are significant attempts made to theoretically understand the process performance [11][12][13][14][15][16][17][18]. Xiu et al [11] developed a mathematical model to describe the sorption-enhanced SR in a fixed bed.…”
Section: Nomenclaturementioning
confidence: 99%
“…They obtained a CH 4 conversion of 65% and an average H 2 purity up to 80% with traces of CO and CO 2 . Using more reactor length, Xiu et al [12] reached 88% H 2 purity and less than 30 ppm CO. Kapil et al [16] developed heterogeneous bulk scale and particle scale models. They found that the H 2 purity and productivity at bulk scale are sensitive to wall temperature, bed voidage, and feed composition.…”
Section: Nomenclaturementioning
confidence: 99%